Investigating the Ability to Perform Basic and Instrumental Activities of Daily Living in Elderly Women With Osteoporosis in Tehran, Iran - Farideh Bastani; Zohreh Sadat Dolatabadi Arani; Hamid Haghani; Farzaneh Mehdipour; Hossein Jahani (Iran University of Medical Sciences, 2023)
Background & Aims Aging is associated with decreased physical and psychological functions. This study aims to investigate the ability to perform basic and instrumental activities of daily living (ADL) in elderly women with osteoporosis in Tehran, Iran. Materials & Methods This is a cross-sectional study conducted on 130 elderly women over 60 years of age referred to selected hospitals affiliated to Iran University of Medical Sciences in 2019-2020, who were selected by a consecutive sampling method. The data collection tools were a demographic form, the Barthel index for ADL, and the Lawton-Brody Instrumental ADL scale. The data was statistically analyzed in SPSS software, version 20. Results The mean age of the women was 67.5±5.7 years. None of them had dependency for performing ADLs such as eating. The highest dependence was for urination (54.62%). Regarding instrumental ADLs, the highest inability was related to shopping (60.77%), and the lowest inability was related to managing one's own medication use (0.77%). The scores of basic and instrumental ADLs were significantly related to age and educational level (P<0.001). Conclusion More governmental, family and social support is needed for elderly women with osteoporosis (with older age and educational level) who have lower ability to perform their basic and instrumental ADLs.